Ù†ØÙˆ ØªÙØ³ÙŠØ± Ø¨Ù„Ø§ØºÙŠ Ø¬Ø¯ÙŠØ¯ Ù„Ù„Ù†Øµ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ› Ø¨Ø¹Ø¶ Ø£Ù„ÙØ§Ø¸ Ø³ÙˆØ±Ø© Ø§Ù„Ù†Ø³Ø§Ø¡ Ø£Ù†Ù…ÙˆØ°Ø¬Ø§ - Elsayed Mohamed Salem Alawadi (UIN Siber Syekh Nurjati Cirebon, 2020)
ÙƒØ«Ø± Ø§Ù„ÙƒÙ„Ø§Ù… ØÙˆÙ„ Ø§Ù„ØªØ¬Ø¯ÙŠØ¯ØŒ ÙˆØ§Ù„ØªØ®Ù„ÙŠ Ø¹Ù† Ø£Ø¯ÙˆØ§Øª Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ù‚Ø¯ÙŠÙ…Ø©ØŒ ÙˆØ§Ù„Ø¨ØØ« Ø¹Ù† ØºÙŠØ±Ù‡Ø§ Ù„ØªÙ‚Ø¯ÙŠÙ… ØªÙØ³ÙŠØ± ÙŠØªÙˆØ§ÙÙ‚ Ù…Ø¹ Ø¬Ù„Ø§Ù„Ø© Ø§Ù„Ù†Øµ ÙˆÙ…ÙˆØ§ÙƒØ¨Ø© Ø§Ù„Ø¹ØµØ±ØŒ ÙˆØ¥Ù† ÙƒØ§Ù†Øª ÙƒØªØ¨ Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ù‚Ø¯ÙŠÙ…Ø© Ù‚Ø¯ ÙˆÙÙ‘Øª Ø¨ØØ§Ø¬Ø© Ø§Ù„Ø£Ø²Ù…Ù†Ø© Ø§Ù„ØªÙŠ ØµÙ†Ø¹Øª ÙÙŠÙ‡Ø§ ØªÙ„Ùƒ Ø§Ù„ÙƒØªØ¨ØŒ ÙÙ‡Ùˆ Ù„Ø§ ØªÙÙŠ Ø¨ØØ§Ø¬Ø© Ù‡Ø°Ø§ Ø§Ù„Ø²Ù…Ø§Ù†Ø› Ø¥Ø° Ù‡ÙŠ Ø¯Ø§Ø¹ÙŠØ© Ø¥Ù„Ù‰ Ù‚ÙˆÙ„ Ø£Ø¬Ù…Ø¹ØŒ ÙˆØ¨ÙŠØ§Ù† Ø£ÙˆØ³Ø¹ØŒ ÙˆØ¨Ø±Ù‡Ø§Ù† Ø£Ù†ØµØ¹ ÙÙŠ Ø£Ø³Ù„ÙˆØ¨ Ø£Ø¬Ø°Ø¨ Ù„Ù„Ù‚Ù„Ø¨ØŒ ÙˆØ£Ø®Ù„Ø¨ Ù„Ù„Ù‘ÙØ¨ØŒ ÙˆØ£ØµØºÙ‰ Ù„Ù„Ø£Ø³Ù…Ø§Ø¹ØŒ ÙˆØ£Ø¯Ù†Ù‰ Ù„Ù„Ø¥Ù‚Ù†Ø§Ø¹ØŒ ÙŠØªÙ†Ø§Ø³Ø¨ Ù…Ø¹ Ø¹Ù‚ÙˆÙ„ ÙˆØ£ÙÙ‡Ø§Ù… Ù‡Ø°Ø§ Ø§Ù„Ø²Ù…Ø§Ù†ØŒ ÙˆØ£Ø¯Ø¹Ù‰ Ù„Ù„Ø¥Ù‚Ø¨Ø§Ù„ Ø¨Ø·Ø±ÙŠÙ‚ Ø£Ø³Ù‡Ù„ØŒ ÙˆØ¹Ø±Ø¶ Ø£ÙŠØ³Ø±. ÙˆÙ…Ù† Ù‡Ù†Ø§ Ø¬Ø§Ø¡ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ØÙ„Ù‚Ø© Ù…Ù† ØÙ„Ù‚Ø§Øª Ø§Ù„Ø¬Ù‡ÙˆØ¯ Ø§Ù„Ù…Ø¨Ø°ÙˆÙ„Ø© Ø¹Ø¨Ø± Ø§Ù„ØªØ§Ø±ÙŠØ® Ù„Ø¨ÙŠØ§Ù† ÙˆØªÙØ³ÙŠØ± Ø¥Ø¹Ø¬Ø§Ø² Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… Ù„ÙØªÙØ«Ù’Ø¨ÙØªÙŽ Ø³Ø± ØªÙØ±Ø¯ Ø¨Ø¹Ø¶ Ø£Ù„ÙØ§Ø¸ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ…ØŒ ÙˆØ¨ÙŠØ§Ù† Ø¬Ù…Ø§Ù„ÙŠØ§ØªÙ‡Ø§ ÙˆØ¥Ø¸Ù‡Ø§Ø± Ø¨Ù„Ø§ØºØªÙ‡Ø§ØŒ ÙˆØ±ÙˆØ¹Ø© Ø³Ø¨ÙƒÙ‡Ø§ØŒ ÙˆØ§ØªØ³Ø§Ù‚Ù‡Ø§ Ù…Ø¹ Ù…Ø§ ÙˆØ±Ø¯Øª ÙÙŠÙ‡ Ø³ÙŠØ§Ù‚Ø§Øª Ù…ØªØ¹Ø¯Ø¯Ø© Ù…Ù† Ø¬Ù…ÙŠØ¹ Ø²ÙˆØ§ÙŠØ§Ù‡. ÙˆØ³ÙŠØ³ØªØ¹ÙŠÙ† Ø§Ù„Ø¨ØØ« Ø¨Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªÙƒØ§Ù…Ù„ÙŠ Ø§Ù„Ø°ÙŠ ÙŠÙ…Ø²Ø¬ Ø¨ÙŠÙ† Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠ Ø§Ù„Ø°ÙŠ ÙŠØªØªØ¨Ø¹ Ø§Ù„Ø¸Ø§Ù‡Ø±Ø© ÙÙŠ Ø£ØµÙ„ Ù†Ø´Ø£ØªÙ‡Ø§ØŒ ÙˆØ£ÙˆÙ„ Ù…Ù† Ø£Ø·Ù„Ù‚Ù‡Ø§ ÙˆØ§Ø³ØªØ¹Ù…Ù„Ù‡Ø§ Ù…Ø±ÙˆØ±Ø§Ù‹ Ø¨Ù‡Ø§ Ø¹Ø¨Ø± Ø§Ù„Ø£Ø²Ù…Ù†Ø© Ø¥Ù„Ù‰ Ù…Ø§ Ø§Ø³ØªÙ‚Ø±Øª Ø¹Ù„ÙŠÙ‡ Ø§Ù„Ø¢Ù† ØŒ ÙˆØ§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠ Ø§Ù„Ù„ØºÙˆÙŠ ÙˆØ§Ù„Ø°ÙŠ ÙŠÙÙŠØ¯ ÙÙŠ ØªØÙ„ÙŠÙ„ Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ù„ØºÙˆÙŠØ§Ù‹ Ù„Ø¥Ø¯Ø±Ø§Ùƒ Ø§Ù„Ù…Ø¹Ù†Ù‰ØŒ Ø«Ù… Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„Ø°ÙŠ ÙŠØ±ØµØ¯ Ø®ØµØ§Ø¦Øµ Ø§Ù„Ø¸Ø§Ù‡Ø±Ø© ÙˆÙ…Ù„Ø§Ù…ØÙ‡Ø§ØŒØ«Ù… Ø¨ÙŠØ§Ù† Ù‡Ø°Ø§ Ø§Ù„ØªÙØ±Ø¯ØŒ ÙˆØ¢Ø«Ø§Ø±Ù‡ Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ©ØŒ ÙˆÙ‚ÙŠÙ…ØªÙ‡ Ø§Ù„Ø¬Ù…Ø§Ù„ÙŠØ©. ÙˆØ³Ø±Ù‡ Ø§Ù„Ø¨ÙŠØ§Ù†ÙŠ Ø§Ù„Ø°ÙŠ ÙŠØ¹ØªØ¨Ø± Ø¹Ù…Ù„Ø§Ù‹ ÙÙ†ÙŠØ§Ù‹ Ø®Ø§Ù„ØµØ§Ù‹ ÙŠÙ†Ø·ÙˆÙŠ ØªØØª Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙÙ†ÙŠ. ÙˆØ¹Ù„ÙŠÙ‡ Ø¬Ø§Ø¡Øª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ÙÙŠ Ù…Ù‚Ø¯Ù…Ø© ÙˆØªÙ…Ù‡ÙŠØ¯ ØÙˆÙ„ Ø§Ù„ØªØ¬Ø¯ÙŠØ¯ ÙÙŠ Ø¹Ù„Ù… Ø§Ù„ØªÙØ³ÙŠØ±ØŒ ÙˆØ§Ù„Ù…Ø¨ØØ« Ø§Ù„Ø£ÙˆÙ„ ÙÙŠ Ù…Ø¹Ù†Ù‰ Ø§Ù„ØªØ¬Ø¯ÙŠØ¯ ÙˆØ§Ù„ØªÙØ³ÙŠØ±ØŒ ÙˆØ§Ù„Ø«Ø§Ù†ÙŠ ÙÙŠ ØªØ¬Ø¯ÙŠØ¯ Ø§Ù„ØªÙØ³ÙŠØ±ØŒ ÙˆØ§Ù„Ø«Ø§Ù„Ø« Ù†Ù…ÙˆØ°Ø¬ Ù„ØªÙØ³ÙŠØ± Ø¨Ù„Ø§ØºÙŠ Ø¬Ø¯ÙŠØ¯ØŒ Ø«Ù… Ø®Ø§ØªÙ…Ø© Ù…Ø´ÙÙˆØ¹Ø© Ø¨Ù…ØµØ§Ø¯Ø± Ø§Ù„Ø¨ØØ« ÙˆÙ…Ø±Ø§Ø¬Ø¹Ù‡. ÙˆÙ„Ø¹Ù„ÙŠ Ø¨Ù‡Ø°Ø§ Ø£Ø¶ÙŠÙ Ø§Ù„ØªÙØ§ØªØ© Ø¬Ø¯ÙŠØ¯Ø© Ù„Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ©ØŒ ÙˆÙØ§Ø¡Ù‹ Ù„Ù„Ù‚Ø±Ø¢Ù† ØŒ ÙˆØ¥Ø«Ø±Ø§Ø¡Ù‹ Ù„Ù„ØºØªÙ‡ .Â There is much talk about renewal, abandoning the old tools of interpretation, and looking for others to provide an interpretation that is compatible with the Majesty of the text and keeping up with the times, although the old books of interpretation have fulfilled the times when they were made, they do not meet the need of this time; The first is to say a lot, a broader statement, a proof that is in a way that attracts the heart, a liar, a sore, a listen, a less persuasion, fits in with the minds and thoughts of this time, and an easier way to present the reception. This research came from a series of efforts made throughout history to explain and interpret the Qur'an's miracles to prove the uniqueness of some of the Holy Qur'an's words, to illustrate its esthetics and to show its language, the awe of its scope and its consistency with the various contexts in which it was mentioned. The research will use the complementary approach, which combines the historical approach that follows the phenomenon in its origin, and the first to launch and use it through times to its stability The language analysis approach, which is useful in parsing words to understand meaning, then the descriptive approach that monitors the characteristics and features of the phenomenon, then the uniqueness, its rhetorical effects, and its esthetic value. His graph, which is a work of art, is involved under the technical curriculum. The study thus came in the introduction to and the beginning of the innovation in the science of interpretation, the first in the meaning of renewal and interpretation, the second in the renewal of interpretation, the third in the model of interpretation of a new communication, and the final, with the sources and references of research. This is not to say that the new chapter of Qur'anic studies, in fulfillment of the Qur'an, and enrichment of its language, has been added.